The burden of low back pain in Malta at a population level. (30th September 2020) - Cuschieri, S; Calleja, N; Gorasso, V; Devleesschauwer, B
Abstract: Background: Low back pain (LBP) is a leading global cause of all-age years lived with disability (YLD). Studies conducted in Malta reported that musculoskeletal complaints were the commonest in primary care. The aim was to estimate for the first time the burden of LBP at population level in Malta in terms of disability-adjusted life years (DALYs) and compare to estimates obtained by the Global Burden of Disease (GBD) study. Methods: LBP prevalence data were obtained from the Maltese European Health Interview Survey dataset for 2015 through representative self-reported history of chronic LBP for 12 months in combination to the extent of daily activities limitation. Proportions of LBP severity (with and without leg pain -mild, moderate, severe and most severe) and their corresponding disability weights followed values reported in GBD study. YLDs for LBP were estimated for the whole population by sex. Since LBP does not carry any mortality, YLDs reflected DALYs. The estimated local DALYs per100, 000 were compared to the GBD study for Malta for the same year. Results: Point prevalence of LBP causing a limitation was of 6.3% (5.6% males; 7.0% females), contributing to a total of 27, 006 Maltese suffering from LBP. Global LBP DALYs were of 783 per100, 000. Females experienced higher LBP burden per100, 000 (876 DALYs) than males (689 DALYs). On comparing these DALYs to those reported by GBD study, a discrepancy was observed per 100, 000 (Global LBP 1, 828 DALYs; Males 1, 657 DALYs; Females 1, 999 DALYs). Conclusions: LBP imposes substantial burden in Malta, which is expected to increase with the ageing population. Since etiology of LBP is multifactorial, it is suggested that a multi-disciplinary targeted preventive and management approach is considered. Differences observed between local estimates and those of the GBD study suggest the integration of locally sourced data into the model in order to improve the DALYs estimates of each country. Key messages: Low back pain is a public health burden. Locally sourced data is suggested to be integrated with the GBD study to improve the DALYs estimation for each country.